Recent advances in developing specific therapies for haemophilia. (23rd January 2018) - Ling, Gavin; Nathwani, Amit C.; Tuddenham, Edward G. D.
Summary: Haemophilia therapy has undergone very rapid evolution in the last 10 years. The major limitation of current replacement therapy is the short half‐life of factors VIII and IX. These half‐lives have been extended by the addition of various moieties, allowing less frequent infusion regimens. Entirely novel approaches have also entered the clinic, including a bispecific antibody that mimics factor VIII and strategies that rebalance the haemostatic mechanism by reducing antithrombin through inhibition of synthesis. These two treatments are available by subcutaneous injection at infrequent intervals and both can be used in patients with neutralising antibodies (inhibitors). Finally, a cure may be on the horizon with preliminary evidence of success for gene therapy in haemophilia B and A.